What is the solution to the equation log2 (5x - 2) = 3?

Answers

Answer 1

From log BNE to BEN

X=2

if you want explaination then ask me


Related Questions

For questions 1-2 identify the zeros of the function

Answers

Answer:

Step-by-step explanation:

The zeros of a function are where it crosses the x axis, so just find the coordinates for the x intercepts.

1.

[tex](2,0)[/tex] and [tex](-1,0)[/tex]

2.

[tex](3,0)[/tex] and [tex](-3,0)[/tex]

what are the minimum, first quartile, 20 70 13 15 23 17 40 51

Answers

Answer:

Minimum 13

First quartile 16

Step-by-step explanation:

Rewrite the sample 20 70 13 15 23 17 40 51 in ascending order:

13  15  17  20  23  40  51  70

The minimum is 13.

The median is the middle number

13  15  17  20  23  40  51  70

The middle number between 20 and 23 is

[tex]\dfrac{20+23}{2}=21.5[/tex]

Consider first half of the sample

13  15  17  20

The first quartile is the middle number of this part. The middle number of

13  15  17  20

is

[tex]\dfrac{15+17}{2}=16[/tex]

i am a number. my number squared is equal to 1/16. hat number am i

Answers

Answer: 1/4

Step-by-step explanation: 1/4 x 1/4= 1/16

what is the question mark represent
15/100=375/?

Answers

hey so here ya go, ? = 2500 :)

Answer:

56.25

Step-by-step explanation:

A simple way to answer questions like these is to

Step 1: Multiply 15 and 375. This equals = 5625

Step 2: divide 100 and 5625. This equals = 56.25

Assume that two chords in a given circle are congruent. Which of the following must also be true?

Answers

Answer:

If the two chords are congruent, then they must be equidistant from the centre of the circle. 

Ans: D

The diagram attached below shows that if two congruent chords are in a given circle, a statement that will be true is:

the two congruent chords must be equidistant from the center of the circle.

Facts about congruent chords in a given circle:

The diagram attached below shows two chords that have the same length in the given circle O.

The diagram shows that distance from the midpoint of one chord to the center of the circle, O, is the same as the distance from the middle of the other chord to center, O.

The diagram attached below therefore shows that if two congruent chords are in a given circle, a statement that will be true is:

the two congruent chords must be equidistant from the center of the circle.

Learn more here:

https://brainly.com/question/2364467

The distance between the points (5, -2) and (-7, 3) is

Answers

For this case we have that the distance between two points is given by:

[tex]d = \sqrt {(x_ {2} -x_ {1}) ^ 2+ (y_ {2} -y_ {1}) ^ 2}[/tex]

We have the points:

[tex](x_ {1}, y_ {1}) = (5, -2)\\(x_ {2}, y_ {2}) = (- 7,3)[/tex]

Substituting:

[tex]d = \sqrt {(- 7-5) ^ 2 + (3 - (- 2)) ^ 2}\\d = \sqrt {(- 7-5) ^ 2 + (3 + 2) ^ 2}\\d = \sqrt {(- 12) ^ 2 + (5) ^ 2}\\d = \sqrt {144 + 25}\\d = \sqrt {169}\\d = 13[/tex]

Thus, the distance between the points is 13

Answer:

[tex]d = 13[/tex]

What is the simplified form of this expression?

Answers

Answer:

[tex]\large\boxed{7c^2d-7c+4d-10}[/tex]

Step-by-step explanation:

[tex]5c^2d-4c+3d-3+2c^2d-3c+d-7\qquad\text{combine like terms}\\\\=(5c^2d+2c^2d)+(-4c-3c)+(3d+d)+(-3-7)\\\\=7c^2d-7c+4d-10[/tex]

Julien interviewed his classmates on which course they prefer and which animal they prefer. What percentage of cat lovers also prefer French?

Answers

Answer:

66.6%

Step-by-step explanation:

complementary or supplement and also solve for X. ​

Answers

Answer:

see explanation

Step-by-step explanation:

The 2 indicated angles form a straight angle and are supplementary.

4x + 5 + 41 = 180

4x + 46 = 180 ( subtract 46 from both sides )

4x = 134 ( divide both sides by 4 )

x = 33.5

solve using the elimination method -4x+2y=8 4x+4y=28​

Answers

Answer:

x = -1

y = 6

Step-by-step explanation:

Equation (1) : -4x + 2y = 8

Equation (2) : 4x + 4y = 28​

(1) + (2):

6y = 36

y = 6

Sub y = 6 into (1):

-4x + 2(6) = 8

-4x + 12 = 8

-4x = -4

x = -1

HELPPPPPPPPPP Add & subtract matrices .....

PLZ GIVE THE ANSWER .. THANKSSSSS .

Answers

Answer:

[tex]\left[\begin{array}{cc}0&-1\\-1&0\\-1&-1\end{array}\right][/tex]

Step-by-step explanation:

In this question we have to subtract the corresponding entries of column of matrix 1 and the matrix 2 corresponding entries

[tex]=\left[\begin{array}{cc}-1&0\\1&-2\\1&3\end{array}\right]-\left[\begin{array}{cc}-1&1\\2&-2\\2&4\end{array}\right] \\=\left[\begin{array}{cc}-1-(-1)&0-1\\1-2&-2-(-2)\\1-2&3-4\end{array}\right]\\=\left[\begin{array}{cc}-1+1&-1\\-1&-2+2\\-1&-1\end{array}\right]\\=\left[\begin{array}{cc}0&-1\\-1&0\\-1&-1\end{array}\right][/tex]

Select the expression that is equivalent to (x-3)^2

Answers

The answer is C. X^2-6x+9

Answer:

C. [tex]x^2-6x+9[/tex]

Step-by-step explanation:

We have the expression [tex](x-3)^2[/tex] we can rewrite it as:

[tex](x-3)^2=(x-3)(x-3)[/tex] and solve it with distributive property or we can use the formula to multiply a binomial by itself. The formula is:

[tex](a+b)^2=a^2+2ab+b^2[/tex]

or

[tex](a-b)^2=a^2-2ab+b^2[/tex]

Then:

[tex](x-3)^2=x^2-2.x.3+3^2\\(x-3)^2=x^2-6x+9[/tex]

The correct option is C. [tex]x^2-6x+9[/tex]

Yuma is solving the inequality 3x−23≥−5.

To solve the inequality, he begins by solving the equation as shown.

Which number line represents the solution to the inequality?

Urgent answer plz. Thank u.

Answers

[tex]3x \geqslant 23 - 5 \\ 3x \geqslant 18 \\ x \geqslant 6 \\[/tex]

Answer:      x≥ 6

Step-by-step explanation:

To solve this inequality

3x - 23 ≥ -5

First, what you need to do is to add 23 to both-side of the inequality, Hence;

3x  -23  +  23  ≥ -5 + 23

(-23 + 23  = 0,   also  -5 +  23  = 18)

3x   ≥   18

To get the value of x, we need to divide both-side of the inequality by 3

3x /  3       ≥   18/3

(On the left hand side of the equation, the three at the numerator will cancel out that of the denominator, then on the right hand side of the equation, 3 will divide 18 which will give 6)

x ≥    6

hello please help asap ( 15 points)

Answers

First 816

second 143

Third 4207.5

find the area of the figure

50cm^2
127cm^2
144.5cm^2
172cm^2

Answers

Answer:

this gives you 144.5cm^2 and that is your answer

I hope my answer has come to your helpanswerStep-by-step explanation:

The area of the given figure is Option(C) 144.5 square centimeter.

What is the area of the given figure in the diagram ?

In the diagram given aside, two shapes are mentioned one is a rectangle and other is a right-angled triangle.

The area of the rectangle is given by -  length*breadth

The area of the right-angled triangle is given by -  1/2*base*height

In the given figure, length = 13cm , breadth = 9cm , base = 11cm and height = 5cm

⇒ Total area = length*breadth + 1/2*base*height

⇒ Total area = 13*9 + 1/2*11*5 square centimeter

⇒ Total area = 117 + 27.5 square centimeter

∴  Total area = 144.5 square centimeter

Therefore, the area of the given figure is Option(C) 144.5 square centimeter.

To learn more about area of figure, refer -

https://brainly.com/question/1090412

#SPJ2

Ky wants to buy three shirts, which were originally priced 49.96 each. The store will discount the price of the third shirt by 50% and then apply a 7.1% tax to the total cost of all three shirts. Including the tax, what will be the mean cost of each shirt?

Answers

49.96 + 49.96 + (49.96x.5)

99.92+24.94=124.86 divide 7.1 and 124.86 which gives you 17.58591549295775 but I’m guessing u round so 17.59 and add that to 124.86which equals 142.45. The total cost is 142.45. But each shirt is 49.96 and the third is 24.94. Don’t forget the dollar sign and have a good day! :)

Answer:

it's 44.59

Step-by-step explanation:

Find the radius of the circle whose equation is x^2 + y^2 = 4.

Answers

Answer:

Radius of the given circle is r = 2.

Step-by-step explanation:

Given equation of the circle is [tex]x^2 + y^2 = 4[/tex].

Now we need to find the radius of the given circle [tex]x^2 + y^2 = 4[/tex].

To find that let's compare with the formula of the circle with is [tex]x^2 + y^2 = r^2[/tex], where r is the radius.

We get [tex]r^2 = 4[/tex]

take square root of both sides.

[tex]r=2[/tex]

Hence radius of the given circle is r = 2.

ANSWER

The radius is 2

EXPLANATION

The given equation of the circle is

[tex] {x}^{2} + {y}^{2} = 4[/tex]

.This is the same as

[tex]{x}^{2} + {y}^{2} = {2}^{2} [/tex]

We campare to the equation of the circle with center at the origin.

[tex]{x}^{2} + {y}^{2} = {r}^{2} [/tex]

We have

[tex]r = 2[/tex]

.Hence the radius of the circle is 2

Find the first three iterates of the function f(z) = 2z + (3 - 2i) with an initial value of z0 = 4.

Answers

Answer:

First Iterate: 11-2i

Second Iterate: 25-6i

Third Iterate: 53-14i

Step-by-step explanation:

Given:

f(z)=2z+(3-2i)

And  

z_0=4

For the first iterate we have to put the value of z0 into the function in place of z.

First Iterate:

z_1=f(z_0 )=2z_0+(3-2i)

=2(4)+(3-2i)

=8+3-2i

=11-2i

Second Iterate:

For the second iterate we have to put the value of z1 into the function in place of z.

z_2=f(z_1 )=2z_1+(3-2i)

=2(11-2i)+(3-2i)

=22-4i+3-2i

=25-6i

Third Iterate:

For the third iterate we have to put the value of z2 into the function in place of z.

z_3=f(z_2 )=2z_2+(3-2i)

=2(25-6i)+(3-2i)

=50-12i+3-2i

=53-14i

Answer:d

Step-by-step explanation:

Cuz

Number 14 please! An Astronaut standing on the moon would weigh about 16% of her weight on earth. If an astronaut Weighs 150 pounds on earth, about how much would she weigh on the moon?

Answers

Answer: 24 pounds

weight on moon=(.16)(weight on earth)

weight on moon= (.16)(150)=24

For the right triangle shown, what is the tangent of angle A?
A) 2/3
B) 3/2
C) 3/4
D) 4/3

Answers

Answer:

The correct answer is option C   3/4

Step-by-step explanation:

It is given a right angled triangle ABC

To find the value of x

Hypotenuse² = Base² + height²

(x + 2)² = x² + (x + 1)²

x² + 4x + 4 = x² + x² + 2x + 1

x² -2x -3 = 0

We get x = 3 and x = -1

We take positive value x = 3

To find Tan A

Tan A = Opposite side/Adjacent side

 = BC/AB = x/(x + 1) = 3/4

Therefore the correct answer is option C.   3/4

Which of the following integers represents the opposite of the opposite of 4?

4
-4
1/4
-1/4

Answers

Answer:

[tex]4[/tex]

Step-by-step explanation:

To find the opposite of the opposite, multiply the given number by -1 twice, or just 1 since [tex]-1*-1=1[/tex].

[tex]4*-1*-1=4[/tex] or [tex]4*1=4[/tex]

Final answer:

The opposite of a number is its additive inverse. Therefore, the opposite of the opposite of a given number will always be the original number itself. In this instance, the opposite of the opposite of 4 is 4.

Explanation:

The question asks for the opposite of the opposite of a given number. In mathematics, the 'opposite' of a number is its additive inverse. If the original number is positive, its opposite is the same number as a negative. Vice versa, if the original number is negative, its opposite would be positive. For example, the opposite of 4 is -4 and the opposite of -4 is 4.

So let's apply this concept to the given number, which is 4. The opposite of 4 is -4. Now, the opposite of -4 is 4. Hence, the opposite of the opposite of 4 is 4.

Learn more about Opposites in Mathematics here:

https://brainly.com/question/36830748

#SPJ2

1.
Identify the hypothesis and conclusion of this conditional statement:

If two lines intersect at right angles, then the two lines are perpendicular.

Hypothesis: The two lines are not perpendicular.
Conclusion: Two lines intersect at right angles.

Hypothesis: Two lines intersect at right angles.
Conclusion: The two lines are not perpendicular.

Hypothesis: The two lines are perpendicular.
Conclusion: Two lines intersect at right angles.

Hypothesis: Two lines intersect at right angles.
Conclusion: The two lines are perpendicular.

Answers

it is the second one

Answer: Hypothesis: Two lines intersect at right angles.

Conclusion: The two lines are not perpendicular.

Step-by-step explanation:

A conditional statement is written as "if p then q" , where symbol 'p' represents the hypothesis and symbol 'q' represents the conclusion.

For example : If a coin has two heads , then the coin is biased.

here , Hypothesis : a coin has two heads

Conclusion : coin is biased

Given conditional statement : If two lines intersect at right angles, then the two lines are perpendicular.

Here, Hypothesis: Two lines intersect at right angles.

Conclusion: The two lines are not perpendicular.

A set of stairs is being built as shown. The length of each stair is 11 inches. What is the rise, r, for each stair? Round to the nearest inch.

2 inches
7 inches
17 inches
24 inches

Answers

Answer:

7 inches just took test

Step-by-step explanation:

The rise, r, for each stair is 7 inches.

What is Trigonometry?

Trigonometry is a branch of mathematics that studies relationships between side lengths and angles of triangles.

From the given figure the  length of each stair is 11 inches.

We have to find the rise of each stair.

From the pythagoras theorem we find the value of r.

In a right-angled triangle, the square of the hypotenuse side is equal to the sum of squares of the other two sides“.

11²+r²=13²

121+r²=169

r²=169-121

r²=48

Take square root on both sides

r=6.9

r= 7 inches.

Hence, the rise, r, for each stair is 7 inches.

To learn more on trigonometry click:

https://brainly.com/question/25122835

#SPJ2

a restaurant owner has a large trash container in the shape of a rectangular prism with a height of 4 ft and a base that is 4 ft wide by 6 feet long. during a one month period the container needed to be empty 4 times. how many cubic feet of trash were taken away during the month?

96 ft^3

192 ft^3

288 ft^3

384 ft^3​

Answers

Answer:384ft^3

Step-by-step explanation:

4x4=16x6=96x4=384^3

Answer:

D) 384

Step-by-step explanation:

i just took the test

Slove -4(x+1)-3=(x-4)

Answers

Answer:

[tex]x=-\frac{3}{5}[/tex]

Step-by-step explanation:

[tex]-4(x+1)-3=(x-4) \\ \\ -4x-4-3=x-4 \\ \\ -4x-7=x-4 \\ \\ -7=5x-4 \\ \\ 5x=-3 \\ \\ x=-\frac{3}{5}[/tex]

- 4 ( x + 1) - 3 = ( x - 4)

Distribute- 4x - 4 - 3 = (x - 4)

    2. Take away the parenthesis at the end

- 4x - 4 - 3 = x - 4

    3. Combine like terms

- 4x - 7 = x - 4

    4.  Add 4x to each side

-7 = -3x - 4

    5. Add 4 to each side

-3 = -3x

    6.  Divide

-3 / -3 = -3x / -3x = 1

does anyone know any of these bc my brother needs help and i don’t know!?!?!?

Answers

Answer:

the third one all the way to the right

Step-by-step explanation:

the other two have two or more congruent sides and that one doesnt and also the one that doesn'r belong has a right angle and the others dont

simplify by rationalizing the denominator: 4 over the square root of 10 minus square room of 6 ​

Answers

Answer:

[tex]\large\boxed{\dfrac{4}{\sqrt{10}-\sqrt6}=\sqrt{10}+\sqrt6}[/tex]

Step-by-step explanation:

[tex]\dfrac{4}{\sqrt{10}-\sqrt6}\\\\\text{use}\ (a-b)(a+b)=a^2-b^2\ \text{and}\ (\sqrt{a})^2=a\\\\=\dfrac{4}{\sqrt{10}-\sqrt6}\cdot\dfrac{\sqrt{10}+\sqrt6}{\sqrt{10}+\sqrt6}=\dfrac{4(\sqrt{10}+\sqrt6)}{(\sqrt{10})^2-(\sqrt6)^2}=\dfrac{4(\sqrt{10}+\sqrt6)}{10-6}\\\\=\dfrac{4(\sqrt{10}+\sqrt6)}{4}=\sqrt{10}+\sqrt6[/tex]

The rationalization of the given expression will be equal to

[tex]\dfrac{4}{\sqrt{10}-\sqrt{6}}=\sqrt{10}+\sqrt{6}[/tex]

What is rationalization?

Rationalization is a procedure used in elementary mathematics to remove the irrational number from the denominator.

The rationalization of the given fraction will be :-

[tex]=\dfrac{4}{\sqrt{10}-\sqrt{6}}\times \dfrac{\sqrt{10}+\sqrt{6}}{\sqrt{10}+\sqrt{6}}[/tex]

[tex]\dfrac{4\sqrt{10}+\sqrt{6}}{\sqrt{10}^2-\sqrt{6}^2}=\dfrac{4\sqrt{10}+\sqrt{6}}{10-6}[/tex]

[tex]\dfrac{4\sqrt{10}+\sqrt{6}}{\sqrt{10}^2-\sqrt{6}^2} =\dfrac{4\sqrt{10}+\sqrt{6}}{4}=\sqrt{10}+\sqrt{6}[/tex]

Hence rationalization of the given expression will be equal to

[tex]\dfrac{4}{\sqrt{10}-\sqrt{6}}=\sqrt{10}+\sqrt{6}[/tex]

To know more about rationalization follow

https://brainly.com/question/14261303

#SPJ2

In an experiment, Seth was given a substance known as ammonium carbonate, (NH4)2CO3. Seth connected a bunsen burner to the gas valve using a gas hose. He turned on the gas valve and lit the bunsen burner. Using a test tube, Seth heated a piece of ammonium carbonate. Seth noticed the following:
- Condensation appeared on the sides at the top of the test tube.
- An ammonia smell was coming from the test tube.
Seth continued to light a wooden splint and stick it down the test tube and it immediately was extinguished.

Throughout this experiment, how many signs of chemical changes were observed and actual chemical changes took place?
A) 4
B) 5
C) 6
D) 7

Answers

Answer: B

Step-by-step explanation: do you still need help with this let me know :P

Answer:

B. 5

Step-by-step explanation:

In an experiment, Seth was given a substance known as ammonium carbonate, (NH4)2CO3. Seth connected a Bunsen burner to the gas valve using a gas hose. He turned on the gas valve and lit the Bunsen burner. Using a test tube, Seth heated a piece of ammonium carbonate. Seth noticed the following: - Condensation appeared on the sides at the top of the test tube. (Condensation is not a chemical change, but it was a sign of a chemical change.) - An ammonia smell was coming from the test tube. Seth continued to light a wooden splint and stick it down the test tube and it immediately was extinguished.

The area of the base of a rectangular prism is 36 cm2. The height of the prism is 3
5
6
cm. What is the volume of the prism?

Answers

Answer:

Height 356: 12816 cm3

Height 6: 216 cm3

Height 5: 180 cm3

Height 3: 108 cm3

Step-by-step explanation:

base * height = volume

What is the answer to number 4.

Answers

Answer: 2x-7, 2+4.

Explanation: An expression is a mathematical phrase that has a + or - but no equal sign.

Other Questions
all of the following are non cabinet non beaucratic titles Please help me on this If your in k12 online school are exams at home online or a building 30 points PLEASE HELP WITH MATH PROBLEM The Constitution gives Congress the power to create federal courts A circle has a radius of 16 inches. to the nearest inch, what is the the length of an arc of the circle that is intercepted by a central angle of 80 degrees Preserving _______ ecosystems can improve water quality, limit flood damages, and recharge the groundwater in a watershed. A. agricultural B. wetland C. desert D. forest Control of thirst response due to increased plasma osmolarity by a negative feedback loop rank from the first to the last steps to describe the correct order of events to maintain homeostasis. The energy that pushes children to create, invent, and explore what happens in their lives is part of Erickson's stage called A. trust. B. autonomy. C. separation. D. initiative. Why does a temperature inversion trap smog and prevent it from dispersing factor 15x^3-5x^2+6x-2 by grouping. what is the resulting expression? During winter, the pigment-producing genes of the arctic fox and other arctic animals do not function and the result is a white coat. This is an example of ___________ change due to environmental influence. Describe two applications of transgenic organisms Graph the linear equation. Find three points that solve the equation, then plot on the graph. -2x-3y=-7 How much energy is released when 0.40 mol C6H6(g) completely reacts with oxygen? 2C6H6(g) + 15O2(g) 12CO2(g) + 6H2O(g) kJ The graph of y= - square root of x is shifted 2 units up and 5 units left. Which equation represents the new graph If BC = 6 and AD = 5, find DC. 4 4.5 7.2 Into what four categories does John Green break the Columbian Exchange? A boy yells in a narrow valley. The sound reflects off of a boulder that is 80m away. HOW LONG will it take to hear the echo if the speed of a sound wave is 320 m/s What is the value of x to the nearest tenth?